2019
DOI: 10.1073/pnas.1820820116
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational instabilities in binary granular materials

Abstract: The motion and mixing of granular media are observed in several contexts in nature, often displaying striking similarities to liquids. Granular dynamics occur in geological phenomena and also enable technologies ranging from pharmaceuticals production to carbon capture. Here, we report the discovery of a family of gravitational instabilities in granular particle mixtures subject to vertical vibration and upward gas flow, including a Rayleigh–Taylor (RT)-like instability in which lighter grains rise through hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 40 publications
(40 reference statements)
2
31
0
Order By: Relevance
“…The grain‐grain skeleton is augmented by an EPS skeleton with grains embedded in an EPS matrix (Figure 3g). A Rayleigh‐Taylor instability may also arise, where an upward drag force can increase locally due to a buoyancy effect, which causes channeling of EPS (lighter fluid) to push through denser sands (McLaren et al., 2019). Previous studies have shown the formation of volcano‐like “water escape structures” (McLaren et al., 2019; Nichols et al., 1994), in which the upwelling pore EPS fluid can be squeezed out from the bottom sand structure, along with gas bubbles (Figure ), creating a “vacuum effect” for the pore water, which explains the occurrence of negative pore pressure (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The grain‐grain skeleton is augmented by an EPS skeleton with grains embedded in an EPS matrix (Figure 3g). A Rayleigh‐Taylor instability may also arise, where an upward drag force can increase locally due to a buoyancy effect, which causes channeling of EPS (lighter fluid) to push through denser sands (McLaren et al., 2019). Previous studies have shown the formation of volcano‐like “water escape structures” (McLaren et al., 2019; Nichols et al., 1994), in which the upwelling pore EPS fluid can be squeezed out from the bottom sand structure, along with gas bubbles (Figure ), creating a “vacuum effect” for the pore water, which explains the occurrence of negative pore pressure (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Segregation is commonly observed in granular materials that contain a mixture of particles that differ in size [1][2][3][4], density [5,6], shape [7] or mechanical properties (friction, elasticity) [8,9]. A fundamental understanding of the physics behind segregation in granular materials is not only a scientific curiosity [10][11][12], but also of high relevance for practice. In practical applications such as the mixing of pharmaceutical ingredients [13], the filling (and discharge) of hoppers [14]or the transport of granular media through agitation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Low viscosity suspensions replace high concentration, and high viscosity suspensions and are unstable because of the instability mechanism [4]. The instability in interactions between fluids can develop in several forms [5]. The granular movement process is started with internal fluidization.…”
Section: Introductionmentioning
confidence: 99%